Posttraumatic stress reactions of underground drivers after suicides by jumping to arriving trains; feasibility of an early stepped care outpatient intervention. Issue 5 (20th October 2019) - Giupponi, Giancarlo; Thoma, Heike; Lamis, Dorian; Forte, Alberto; Pompili, Maurizio; Kapfhammer, Hans-Peter
ABSTRACT: Objective : Underground drivers face a considerable risk of running over suicide jumpers on the tracks during their career. These traumatic exposures may lead to major psychological sequelae. Methods : Within an outpatient setting, 50 drivers were consecutively enrolled in a prospective non-controlled trial. A low-intensity, stepped-care approach included: emergency care immediately after the critical accident, comprehensive assessment with a structured clinical interview using the following scales within three days: Composite International Diagnostic Interview (CIDI), Impact of Event Scale (IES), Screening for Somatoform Disorders (SOMS), and Cologne Trauma Inventory (KTI). Results : During a 2-year period, 50 subway drivers were exposed to 66 serious critical accidents (deaths: 39, severe injuries: 27). Rate of acute stress reactions was 48%; rate of acute stress disorders was 30%. Scores of IES and SOMS were significantly increased correspondingly. At 1-month follow-up, PTSD was diagnosed in 24 (ICD-10) and in 9 drivers (DSM-IV), respectively. Major depression ( n = 15) and somatoform disorder ( n = 10) were diagnosed as coexistent to PTSD. Acute stress reaction/acute stress disorder, IES- and SOMS-scores, and previous traumatic exposures during adulthood, but not during childhood, were significantly associated with the risk of PTSD. A majority of drivers ( n = 43) succeeded in reaching complete symptomatic remission and returning to work again within a 6-month period. Seven drivers suffered from long-lasting posttraumatic symptoms causing severe social impairment. Conclusions : A low-intensity, outpatient stepped-care approach may provide support to traumatized underground drivers in their process of posttraumatic remission and recovery.